Bit-allocation and rate-control algorithm for stereo video coding - ZHU Zhong-jie 1; LIANG Feng1; JIANG Gang-yi 2; YU Mei2 (Tongxin xuebao)
A new bit-allocation and rate-control algorithm for stereo video coding was proposed to improve its coding efficiency and stream reliability.The conventional quadric rate-distortion model was improved and a new one was introduced by incorporating the human visual system（HVS） characteristics.Experimental results show that the improved new rate-distortion model is more precise than the conventional one and the proposed new algorithm can efficiently implement bit allocation and rate control according to coding parameters.